2016
DOI: 10.11152/mu.2013.2066.181.sf
|View full text |Cite
|
Sign up to set email alerts
|

Is the spleen stiffness value acquired using acoustic radiation force impulse (ARFI) technology predictive of the presence of esophageal varices in patients with cirrhosis of various etiologies?

Abstract: Aim: This study's aim was to determine the accuracy of the spleen stiffness value acquired using acoustic radiation force impulse (ARFI) technology, to predict the presence of esophageal varices (EVs) in patients with liver cirrhosis of various etiologies. Material and methods: Of the 366 enrolled patients, 192 had hepatitis B virus, 74 had hepatitis C virus, and 100 had alcohol-related cirrhosis. All patients underwent biochemical tests, gastrointestinal endoscopy, and liver and spleen elastography by ARFI. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…However, SSM was indisputably the strongest predictor for all endoscopic aspects of EV, from their presence, to the detection of varices needing treatment. Other studies also found ARFI-SSM to be a unique independent parameter for EV prediction, according to multivariate analysis 48,49 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, SSM was indisputably the strongest predictor for all endoscopic aspects of EV, from their presence, to the detection of varices needing treatment. Other studies also found ARFI-SSM to be a unique independent parameter for EV prediction, according to multivariate analysis 48,49 .…”
Section: Discussionmentioning
confidence: 84%
“…One concern was raised regarding SSM as a complementary method in evaluating the existence of EVs in patients suffering from cirrhosis: the loss of correlation in alcohol induced cirrhosis 49 . Without a clear reason for this result, the authors have considered the smaller dimension of the spleen that characterized alcoholic cirrhosis to be a probable cause, as compared to viral or non-alcoholic steatohepatitis-cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, Park et al demonstrates that the usefulness of spleen elastography in detecting esophageal varices depends on the cause of cirrhosis. According to this study spleen elastography is not a reliable predictor of esophageal varices induced by alcoholic cirrhosis (33) . According to available studies, spleen elastography is not useful in assessing the grade of esophageal varices (27,(33)(34)(35) .…”
Section: Correlation Between Portal Hypertension Esophageal Varices and Spleen Stiffnessmentioning
confidence: 60%
“…According to this study spleen elastography is not a reliable predictor of esophageal varices induced by alcoholic cirrhosis (33) . According to available studies, spleen elastography is not useful in assessing the grade of esophageal varices (27,(33)(34)(35) . Single studies show that spleen stiffness correlates with clinical history of variceal bleeding (36)(37) , but its utility in determining the risk of bleeding from esophageal varices requires further investigation.…”
Section: Correlation Between Portal Hypertension Esophageal Varices and Spleen Stiffnessmentioning
confidence: 60%
“…There are several studies that evaluated VTQ for the assessment of SS, alone [35,56,57] or in comparison with TE [58]. Studies considering HVPG as a reference for evaluating SSM performance revealed a remarkable accuracy of SSM in predicting CSPH [59,60].…”
Section: Point Shear-waves Elastographymentioning
confidence: 99%